Thermosetting resin composition and color filter

The thermosetting resin composition, comprising a specific combination of epoxy group-containing polymer, polyvalent carboxylic acid hemiacetal ester, and silicone surfactant, addresses the challenges of pigment elution, low metal ions retention, and coating defects in color filter protective films by enhancing NMP resistance and coating properties.

JP2025048706APending Publication Date: 2025-04-03NOF CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024053589
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-21
Filing Date
2024-03-28
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

The existing color filter protective films for liquid crystal displays face challenges such as pigment elution due to NMP penetration, insufficient low metal ions retention, and coating defects at low viscosity, especially under high temperatures and high-energy UV exposure.

Method used

A thermosetting resin composition combining a specific epoxy group-containing polymer, a polyvalent carboxylic acid hemiacetal ester, and a silicone surfactant in a specific ratio, which forms a protective film with enhanced NMP resistance, low metal ions retention, and improved coating properties even at low viscosity.

Benefits of technology

The proposed composition effectively suppresses NMP penetration and residual metal ions, while ensuring excellent coating properties and yield, thereby addressing the defects and reliability issues in current color filter protective films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025048706000001
    Figure 2025048706000001
  • Figure 2025048706000002
    Figure 2025048706000002
  • Figure 2025048706000003
    Figure 2025048706000003
Patent Text Reader

Abstract

To provide a thermosetting resin composition which can form a cured film excellent in NMP resistance and low metal ion residual properties and has good coatability at low viscosity, and to provide a color filter using a protective film comprising a cured product of the thermosetting resin composition.SOLUTION: The thermosetting resin composition contains an epoxy compound (A), a polycarboxylic acid hemiacetal ester (B), and a silicone-based surfactant (C). The (A) contains an epoxy group-containing polymer having a monomer (a1), a monomer (a2), and a monomer (a3) as constituent units and having an epoxy equivalent of 155-240 g / mol. The content of the (C) is 0.01-1.0 pt.mass based on 100 pts.mass of the total of the (A) and the (B). The functional group equivalent ratio of carboxyl groups of the (B) to the total epoxy groups of the (A) is in the range of 0.25-0.95.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermosetting resin composition and a color filter having a protective film formed by curing the thermosetting resin composition. [Background technology]

[0002] Color filters used in liquid crystal display devices generally have a structure in which a black matrix layer formed in a predetermined pattern, a colored layer in which red (R), green (G) and blue (B) are arranged in a predetermined order, a protective film, a photospacer and an alignment film are laminated in this order on a transparent substrate.

[0003] Recently, the demands for the display performance of liquid crystal displays have become stricter, and the demands for reliability such as display performance such as brightness, color purity, and contrast for color filters are increasing, as well as the demands for reliability such as preventing a phenomenon called image sticking, in which the image of a display element is fixed, and display unevenness. According to Patent Document 1, the occurrence of the image sticking is said to be influenced by the fact that Na ions and K ions contained in a developer such as potassium hydroxide or sodium carbonate remain on the surface of the protective film during the photospacer formation process. It is considered that these ions are likely to remain due to the influence of polar functional groups such as carboxyl groups and hydroxyl groups that are generated on the protective film surface by pre-coating cleaning such as UV ozone treatment performed on the protective film surface before the photospacer is applied. For this reason, the protective film is required to have the performance to suppress the residue of Na ions and K ions even when it comes into contact with a developer such as potassium hydroxide or sodium carbonate after UV cleaning (hereinafter, low metal ion residue). Patent Document 1 proposes a composition that combines an epoxy group- or oxetanyl group-containing polymer, a polyvalent carboxylic acid hemiacetal ester, a specific epoxy compound, and a difunctional bisphenol A type epoxy resin as a resin composition for a color filter protective film that has excellent low metal ion residual properties.

[0004] In addition, in order to improve the optical properties of displays, the thickness of color filter protective films has been reduced (finished film thickness: about 1.0 μm), and it is necessary to reduce the viscosity of the coating liquid for color filter protective films (3.0 mPa·s or less). However, the lower viscosity of the coating liquid makes it easier for coating defects such as the liquid backflow of the coating liquid at the glass part at the edge of the substrate and the coating film repellency to occur, which causes a problem of reduced yield of color filters. In order to prevent the occurrence of such coating defects, the coating liquid for protective films is required to have excellent coatability even in a low viscosity design. As a resin composition for color filter protective films with excellent coatability, Patent Document 2 proposes a composition that combines an epoxy compound, an epoxy curing agent, an N-alkylmorpholine, and a fluorine-based nonionic surfactant, and Patent Document 3 proposes a composition that combines a multifunctional epoxy resin, a polyvalent carboxylic acid hemiacetal ester, and a monohydric alcohol. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2022-112451 A [Patent Document 2] JP 2011-65051 A [Patent Document 3] Patent Publication No. 2022-26360 Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, in order to expand the color gamut that can be displayed on a liquid crystal display device, the pigments contained in the coloring layer have been made finer and the pigment concentration has been increased. However, this has caused a problem that the pigments pass through the protective film and dissolve into the liquid crystal layer, causing display defects. It is believed that the dissolution of the pigment components occurs through the solvent of the alignment film (N-methyl-2-pyrrolidone, hereinafter referred to as NMP) that permeates the protective film in the alignment film formation process, which is a post-process of the protective film. In this process, the protective film may be exposed to a high temperature of about 180°C in a state where the protective film and NMP are in contact with each other, so the protective film is required to have the ability to suppress the penetration of NMP even at high temperatures (hereinafter referred to as NMP resistance). Note that, in the conventional color filter protective film, it was considered sufficient if it could suppress the penetration of the solvent at about 25 to 40°C, but in order to suppress the dissolution of the above-mentioned pigment components, it is necessary to suppress the penetration of the solvent at a temperature significantly higher than before.

[0007] In addition, the amount of UV irradiation during pre-coating cleaning of the photospacer varies depending on the manufacturer, and manufacturers that use high-energy UV irradiation may still experience problems such as burn-in and uneven display. For this reason, it is necessary to be able to suppress the residual Na ions and K ions even when exposed to higher energy UV light during pre-coating cleaning of the photospacer. Furthermore, with regard to coatability, it is required that coating defects such as backflow of the coating liquid and repelling of the coating film do not occur regardless of the coating method such as spin coating or slit coating. According to the study by the present inventors, the compositions described in Patent Documents 1 to 3 do not sufficiently combine NMP resistance, low metal ion residual property, and coatability.

[0008] The present invention has been made in view of the above-mentioned conventional techniques, and provides a thermosetting resin composition capable of forming a cured film having excellent NMP resistance and low metal ion residual property and having good coatability at low viscosity, and a color filter using a protective film made of the cured product thereof. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors have conducted various investigations to solve the above problems, and as a result have found that the above problems can be solved simultaneously by combining a specific epoxy group-containing polymer, a polyvalent carboxylic acid hemiacetal ester, and a silicone surfactant in a specific ratio range, thereby completing the present invention. That is, the present invention relates to the following [1]-[3].

[0010] [1] A thermosetting resin composition comprising an epoxy compound (A), a polyvalent carboxylic acid hemiacetal ester (B), and a silicone-based surfactant (C), The epoxy compound (A) contains an epoxy group-containing polymer having, as constituent units, (a1) a (meth)acrylate monomer having an epoxy group, (a2) a monomer represented by the following formula (1), and (a3) ​​a monomer represented by the following formula (2), and has an epoxy equivalent of 155 to 240 g / mol: [ka] (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 represents an aryl group or an alicyclic hydrocarbon group having 3 to 12 carbon atoms. [ka] (In the formula, R 3 represents an alicyclic hydrocarbon group having 3 to 12 carbon atoms or an aromatic hydrocarbon group. the silicone surfactant (C) is 0.01 to 1.0 part by mass relative to 100 parts by mass in total of the epoxy compound (A) and the polyvalent carboxylic acid hemiacetal ester (B); A thermosetting resin composition, wherein the functional group equivalent ratio of the carboxyl group of the polyvalent carboxylic acid hemiacetal ester (B) to the total epoxy groups of the epoxy compound (A) is within the range of 0.25 to 0.95.

[0011] [2] The thermosetting resin composition according to [1] above, further comprising an organic solvent, the proportion of the alicyclic ketone organic solvent in the organic solvent being 20% ​​by mass or more and 80% by mass or less.

[0012] [3] A color filter having a protective film formed by curing the thermosetting resin composition according to [1] or [2] above. Effect of the Invention

[0013] According to the thermosetting resin composition of the present invention, a color filter protective film having excellent NMP resistance and low residual metal ions can be formed. In addition, the thermosetting resin composition of the present invention has excellent coatability even at a low viscosity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The thermosetting resin composition of the present invention contains an epoxy compound (hereinafter, component (A)), a polyvalent carboxylic acid hemiacetal ester (hereinafter, component (B)), and a silicone surfactant (hereinafter, component (C)).

[0015] <Component (A)> The component (A) of the present invention contains, as essential components, an epoxy group-containing polymer having an epoxy equivalent of 155 to 240 g / mol and having constitutional units of (a1) a (meth)acrylate monomer having an epoxy group, (a2) a monomer represented by the following formula (1), and (a3) ​​a monomer represented by the following formula (2): The component (A) may be used alone or in combination of two or more types. [ka] (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 represents an aryl group or an alicyclic hydrocarbon group having 3 to 12 carbon atoms. [ka] (In the formula, R 3 represents an alicyclic hydrocarbon group having 3 to 12 carbon atoms or an aromatic hydrocarbon group.

[0016] The (a1) (meth)acrylate monomer having an epoxy group may be any (meth)acrylate monomer having an epoxy group, and any monomer known for such purposes may be used.

[0017] Preferred examples of the (meth)acrylate monomer having an epoxy group include monomers represented by the following formulas (3) to (5). [ka] (In the formula, R 4 represents a hydrogen atom or a methyl group, and k represents an integer of 1 to 3.

[0018] [ka] (In the formula, R 5 is a hydrogen atom or a methyl group, R 6 Ha-CH 2 O-group or -CH 2 -group, R 7 represents a hydrogen atom or an alkyl group having 1 to 2 carbon atoms, and m represents an integer of 1 to 3.

[0019] [ka] (In the formula, R 8 represents a hydrogen atom or a methyl group, and n represents an integer of 1 to 3.

[0020] Among the above formulas (3) to (5), formula (3) is particularly preferably R 4 is a methyl group, k is 1, and as formula (4), R 5 is a hydrogen atom, R 6 Ga-CH 2 O-group, R 7 is a hydrogen atom, m is 1, and as formula (5), R 8 is a methyl group and n is 1.

[0021] (a2) The monomer represented by the following formula (1) can be any known monomer. [ka] (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 represents an aryl group or an alicyclic hydrocarbon group having 3 to 12 carbon atoms.

[0022] Among the above formula (1), R 1 is a methyl group, R 2 is a monomer of an alicyclic hydrocarbon group having six carbon atoms.

[0023] (a3) The monomer represented by the following formula (2) can be any known monomer. [ka] (In the formula, R 3 represents an alicyclic hydrocarbon group having 3 to 12 carbon atoms or an aromatic hydrocarbon group.

[0024] Among the above formula (2), R 3 is a monomer of an alicyclic hydrocarbon group having six carbon atoms.

[0025] The epoxy group-containing polymer can be obtained by copolymerizing at least the components (a1), (a2) and (a3). The polymerization form may be linear or branched, and may be any of a random copolymer, a block copolymer, a graft copolymer, etc.

[0026] The polymerization method for the epoxy group-containing polymer is not particularly limited, and various polymerization methods such as ionic polymerization such as radical polymerization and anionic polymerization can be used. In addition, polymerization methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization can be used. Furthermore, additives such as catalysts and solvents may be added to the polymerization reaction system as necessary.

[0027] The epoxy equivalent of the epoxy group-containing polymer is 155 to 240 g / mol, and preferably 160 to 230 g / mol. By setting the epoxy equivalent within the above range, a sufficient crosslinked structure is obtained, and NMP resistance is improved.

[0028] The weight average molecular weight (Mw) of the epoxy group-containing polymer is not particularly limited, but is, for example, 3,000 to 100,000, preferably 4,000 to 80,000, and more preferably 10,000 to 50,000.

[0029] In addition to the epoxy group-containing polymer, component (A) may contain a polyfunctional epoxy resin. The polyfunctional epoxy resin may be any epoxy resin having two or more epoxy groups in one molecule, and any known material may be used. Examples of polyfunctional epoxy resins include bisphenol A type epoxy resins, bisphenol A novolac type epoxy resins, bisphenol F type epoxy resins, brominated bisphenol A type epoxy resins, bisphenol S type epoxy resins, diphenyl ether type epoxy resins, hydroquinone type epoxy resins, naphthalene type epoxy resins, biphenyl type epoxy resins, fluorene type epoxy resins, phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, trishydroxyphenylmethane type epoxy resins, trifunctional type epoxy resins, tetraphenylolethane type epoxy resins, dicyclopentadiene phenol type epoxy resins, hydrogenated bisphenol A type epoxy resins, bisphenol A nucleus-containing polyol type epoxy resins, polypropylene glycol type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, glyoxal type epoxy resins, alicyclic type epoxy resins, heterocyclic type epoxy resins, etc. The polyfunctional epoxy resins may be used alone or in combination of two or more. Among these, bisphenol A type, bisphenol A novolac type, and alicyclic type epoxy resins are particularly preferred.

[0030] The epoxy group-containing polymer contains, per 100 parts by mass of the epoxy group-containing polymer, preferably 59.2 to 91.7 parts by mass of the (a1) component, preferably 3.0 to 35.0 parts by mass, more preferably 5.0 to 25.0 parts by mass of the (a2) component, and preferably 3.0 to 35.0 parts by mass, more preferably 5.0 to 25.0 parts by mass of the (a3) ​​component.

[0031] The content of the component (A) is preferably 13 to 87 parts by mass, more preferably 15 to 85 parts by mass, and particularly preferably 23 to 77 parts by mass, per 100 parts by mass of the total of the components (A) and (B).

[0032] <(B) component> The component (B) is a vinyl ether-blocked polycarboxylic acid in which the carboxyl group of a polycarboxylic acid compound is rendered latent as a hemiacetal ester by a vinyl ether compound, i.e., blocked. The component (B) may be used alone or in combination of two or more.

[0033] The polycarboxylic acid compound may be any compound having two or more carboxyl groups in one molecule, and any known material may be used. Examples of the polycarboxylic acid compound include cyclobutanetetracarboxylic acid, cyclohexanetricarboxylic acid, trimellitic acid, and pyromellitic acid. Among them, trimellitic acid and pyromellitic acid are preferred from the viewpoint of cured film properties such as NMP resistance. The polycarboxylic acid may be used alone or in combination of two or more.

[0034] The number of carbon atoms excluding the vinyl carbon of the vinyl ether compound is preferably 1 to 6, more preferably 2 to 6. Specific examples of the vinyl ether compound include aliphatic vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, i-propyl vinyl ether, n-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, and cyclohexyl vinyl ether. Among them, n-propyl vinyl ether and i-propyl vinyl ether are preferred because they are easily available and their curing temperature is suitable for the process of the protective film. The vinyl ether compound may be used alone or in combination of two or more.

[0035] Component (B) can be obtained by reacting a polycarboxylic acid compound with a vinyl ether compound at a temperature ranging from room temperature to 150°C. Since the blocking reaction is an equilibrium reaction, adding a certain excess amount of a vinyl ether compound to the polycarboxylic acid compound promotes the reaction and improves the yield. In addition, a catalyst or solvent can be added to the reaction between the polycarboxylic acid compound and the vinyl ether compound depending on the purpose. When the acid value of the reaction solution falls to 2.0 mgKOH / g or less due to the progress of the blocking reaction, it is determined that the reaction has progressed sufficiently and the reaction is terminated.

[0036] Examples of the catalyst include tertiary amines, imidazoles, organic phosphorus compounds, quaternary phosphonium salts, diazabicycloalkenes, organic metal compounds, quaternary ammonium salts, boron compounds, and metal halides. The catalysts can be used alone or in combination of two or more.

[0037] Examples of the solvent include aromatic hydrocarbons, ethers, esters, ether esters, ketones, phosphate esters, nitriles, aprotic polar solvents, and propylene glycol alkyl ether acetates. The solvents can be used alone or in combination of two or more.

[0038] The functional group equivalent ratio of the carboxyl group of the (B) component to the total epoxy group of the (A) component is 0.25 to 0.95, preferably 0.30 to 0.90, and more preferably 0.45 to 0.80. If the functional group equivalent ratio of the carboxyl group to the epoxy group is less than 0.25, sufficient NMP resistance cannot be obtained, and if it exceeds 0.95, low metal ion residual property becomes insufficient. By setting the ratio of the carboxyl group to the epoxy group in the above range and combining it with the (C) component described later, it is possible to achieve both NMP resistance and low metal ion residual property at a high level.

[0039] <(C) component> As the component (C), any known silicone surfactant having a polyorganosiloxane skeleton or the like can be used. Examples of silicone surfactants include polyether-modified products, polyester-modified products, polyol-modified products, and specially modified products. Among them, polyether-modified products are preferred from the viewpoint of compatibility with other organic materials. However, those containing fluorine atoms in the structure are not preferred. Examples of commercially available products of the component (C) include BYK-302 (BYK Japan Co., Ltd.), BYK-307 (same), BYK-330 (same), BYK-333 (same), BYK-348 (same), BYK-361N (same), BYK-392 (same), BYK-399 (same), Polyflow KL-100 (Kyoeisha Chemical Co., Ltd.), KL-400HF (same), KL-401 (same), KL-402 (same), and KL-7. 00 (Shin-Etsu Chemical Co., Ltd.), LE-304 (Shin-Etsu Chemical Co., Ltd.), KP-110 (Shin-Etsu Chemical Co., Ltd.), KP-112 (Shin-Etsu Chemical Co., Ltd.), KP-323 (Shin-Etsu Chemical Co., Ltd.), KP-366 (Shin-Etsu Chemical Co., Ltd.), KP-368 (Shin-Etsu Chemical Co., Ltd.), KF-351A (Shin-Etsu Chemical Co., Ltd.), Disparlon LS-009 (Kusumoto Chemical Co., Ltd.), LHP-91 (Shin-Etsu Chemical Co., Ltd.), 1711EF (Shin-Etsu Chemical Co., Ltd.), Silface SAG003 (Nissin Chemical Co., Ltd.), SAG005 (Shin-Etsu Chemical Co., Ltd.), SAG008 (Shin-Etsu Chemical Co., Ltd.), DOWSIL FZ2122 (Dow Toray Co., Ltd.), 8019 (Shin-Etsu Chemical Co., Ltd.), 8637, etc. The component (C) may be used alone or in combination of two or more kinds.

[0040] The amount of the (C) component is 0.01 to 1.0 part by mass, preferably 0.03 to 0.50 part by mass, and more preferably 0.05 to 0.20 part by mass, based on 100 parts by mass of the total of the (A) and (B) components. If the (C) component is less than 0.01 part by mass, sufficient low metal ion residual properties cannot be obtained, and if it exceeds 1.0 part by mass, the coating properties are reduced. This time, it was newly discovered that the (C) component not only improves the coating properties but also contributes to the low metal ion residual properties, leading to the completion of the present invention. The reason why the low metal ion residual properties are improved by using the (C) component is not clear, but it is speculated that the silicone surfactant segregated on the surface of the cured film probably suppresses the adsorption of metal ions.

[0041] From the viewpoint of improving low residual metal ions, the weight average molecular weight of component (C) is preferably 8,000 to 50,000, more preferably 14,000 to 40,000. When the weight average molecular weight is within the above range, an excellent balance between segregation on the cured film surface and compatibility with other components is achieved.

[0042] The HLB value of the component (C) is preferably 10 or less, and more preferably from 3 to 9. The HLB value is defined by the Griffin method.

[0043] <Weight average molecular weight (Mw)> The weight average molecular weight of the epoxy group-containing polymer and the component (C) can be determined by a GPC method using a sample that is dissolved in tetrahydrofuran to prepare a 0.5 wt% solution and filtered through a 0.20 μm membrane filter, and can be measured under the following conditions. (Measurement conditions) Analytical equipment: HLC-8320GPC (Tosoh Corporation) Column: TSKgel SuperHZM-M (3 columns) (Tosoh Corporation) Column size: 4.6 x 150 mm Eluent: Tetrahydrofuran Flow rate: 0.30mL / min Detector: Differential refractometer Column temperature: 40℃ Standard sample: polystyrene

[0044] <Other additives> To the thermosetting resin composition of the present invention, additives such as surfactants other than the surfactant (C), silane coupling agents, antioxidants, stabilizers, and organic solvents can be added as long as the effects of the invention are not impaired.

[0045] <Silane coupling agent> Silane coupling agents are compounds having an alkoxysilyl group (Si-OR) and a reactive group in one molecule. The reactive group is preferably one having an epoxy group. Examples of silane coupling agents having an epoxy group include 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. These silane coupling agents can be used alone or in combination of two or more.

[0046] <Antioxidants> As the antioxidant, hindered phenol-based antioxidants such as IRGANOX 1010 (BASF), IRGANOX 1035 (same), IRGANOX 1076 (same), IRGANOX 1135 (same), and IRGANOX 1726 (same), can be used.

[0047] <Stabilizer> The stabilizer refers to the excess vinyl ether, which is added for the purpose of improving the yield of the carboxylic acid hemiacetal ester. Specific examples thereof include the vinyl ethers described in the above "<Component (B)>".

[0048] <Organic solvent> The organic solvent is usually added for the purpose of adjusting the viscosity of the thermosetting resin composition, etc. Specific examples of the organic solvent include esters such as amyl acetate and butyl acetate, ether esters such as ethyl ethoxypropionate and 3-methoxy-3-methyl-1-butyl acetate, ketones such as methyl ethyl ketone and cyclohexanone, and glycol derivatives such as propylene glycol monomethyl ether acetate, propylene glycol diacetate, and diethylene glycol ethyl methyl ether.

[0049] In addition, when the difference in polarity between the pixels of the colored layer increases due to the fineness of the pigment contained in the colored layer of the color filter or the increase in the pigment concentration, in the process of forming a protective film on the colored layer, the protective film may be segregated on a specific pixel, causing the protective film to rise and the flatness of the surface to decrease. Therefore, it is preferable that the thermosetting resin composition has excellent flatness when forming a protective film on a colored layer having a difference in polarity between pixels. From this viewpoint, it is preferable that the organic solvent contains at least one alicyclic ketone organic solvent selected from cyclopentanone, cyclohexanone, isophorone, etc. The alicyclic ketone organic solvent may be used alone or in combination of two or more.

[0050] The mechanism by which the flatness is improved by using an alicyclic ketone organic solvent is not clear, but is presumed to be as follows. In the process of forming a protective film on a colored layer, a protective film-forming composition is applied onto the colored layer, the organic solvent is removed, and then baking is performed. At this time, it is presumed that the protective film-forming composition is temporarily highly polarized by the polyvalent carboxylic acid hemiacetal ester being decomposed into a polyvalent carboxylic acid and a vinyl ether by heat, and therefore the protective film-forming composition is segregated onto the highly polar pixels among the pixels of the colored layer. From this, it is presumed that when an alicyclic ketone organic solvent is present in the protective film-forming composition, the alicyclic ketone organic solvent remaining in the protective film-forming composition in a trace amount forms a coordination structure with the polyvalent carboxylic acid at the highly polar carbonyl site in the baking process, and the polyvalent carboxylic acid is protected by a cyclic alkyl group that is low in polarity, flexible, and exhibits steric repulsion, thereby suppressing the high polarization of the protective film-forming composition, thereby suppressing the segregation of the protective film-forming composition onto a specific pixel among the pixels of the colored layer, thereby improving flatness.

[0051] When an alicyclic ketone organic solvent is used, the ratio of the alicyclic ketone organic solvent in the organic solvent is preferably 20% by mass or more and 80% by mass or less, more preferably 25% by mass or more and 70% by mass or less, and even more preferably 30% by mass or more and 60% by mass or less. If the ratio of the alicyclic ketone organic solvent in the organic solvent exceeds 80% by mass, the viscosity of the protective film forming composition increases, and it is likely to be difficult to apply a coating film with a uniform thickness. If the ratio of the alicyclic ketone organic solvent in the organic solvent is less than 20% by mass, it is difficult to obtain the effect of improving flatness.

[0052] (Formation of protective film for color filters) The color filter of the present invention has a layer of a cured product obtained by curing the above-mentioned thermosetting resin composition as a protective film. The thermosetting resin composition is applied so as to cover the colored layer and the black matrix arranged on the substrate. The application method is not particularly limited, and known application methods such as an inkjet method, a spin coating method, and a slit coating method can be used.

[0053] The resulting coating film is dried, and if necessary, pre-heated (hereinafter referred to as "pre-baking"), and then subjected to main curing heating (hereinafter referred to as "post-baking") to form a layer of a resin cured product. In this case, preferred pre-baking conditions include 40 to 140°C and 0 to 1 hour, and preferred post-baking conditions include 150 to 280°C and 0.2 to 2 hours. The heating method is not particularly limited, and for example, a curing device such as a closed curing oven or a tunnel oven capable of continuous curing can be used. The heating source is not particularly limited, and can be hot air circulation, infrared heating, high-frequency heating, or the like. EXAMPLES

[0054] The present invention will be specifically described below with reference to examples and comparative examples. <Polymerization Example 1: Synthesis of epoxy group-containing polymer (A-1)> A four-neck flask equipped with a thermometer, a reflux condenser, a stirrer, and a dropping funnel was charged with 76.0 parts by mass of propylene glycol monomethyl ether acetate (PGMEA) as a solvent, and heated with stirring to 84° C. Then, at a temperature of 84° C., 64.0 parts by mass of glycidyl methacrylate (GMA) as component (a1), 22.0 parts by mass of cyclohexyl methacrylate (CHMA) as component (a2), 14.0 parts by mass of cyclohexyl maleimide (CHMI) as component (a3), 6.0 parts by mass of a peroxide-based polymerization initiator "Perhexyl O (PHO)" manufactured by NOF Corporation as a polymerization initiator, and 18.0 parts by mass of PGMEA were mixed in advance (dropping component) and dropped at a constant speed from the dropping funnel over 2 hours. Thereafter, the temperature was maintained at 84° C. for 5 hours to obtain a 50% PGMEA solution of an epoxy group-containing polymer (A-1) having a weight average molecular weight (Mw) of 21,200 and an epoxy equivalent of 222 g / mol (as active ingredient).

[0055] <Polymerization Examples 2 to 5: Synthesis of epoxy group-containing polymers (A-2 to A-5)> The raw materials shown in Table 1 were mixed under the conditions shown in Table 1, and polymers A-2 to A-5 were obtained in the same manner as in Polymerization Example 1. The charged amount, weight average molecular weight, and epoxy equivalent of each raw material are shown in Table 1.

[0056] [Table 1]

[0057] The abbreviations in Table 1 are as follows. Details of the components (a1), (a2), and (a3) ​​used are shown in Table 2. Component (a1) GMA: glycidyl methacrylate (a2) Component CHMA: Cyclohexyl methacrylate DCPMA: dicyclopentanyl methacrylate (a3) Component CHMI: Cyclohexylmaleimide PhMI: Phenylmaleimide (Polymerization initiator) PHO: t-Hexylperoxy-2-ethylhexanoate (peroxide polymerization initiator manufactured by NOF Corp., product name: Perhexyl O) (solvent) PGMEA: Propylene glycol monomethyl ether acetate

[0058] [Table 2]

[0059] <Comparative Polymerization Examples 1 to 4: Synthesis of Epoxy Group-Containing Polymers (A'-1 to A'-4)> The raw materials shown in Table 3 were mixed under the conditions shown in Table 3, and polymers A'-1 to A'-4 were obtained in the same manner as in Polymerization Example 1. The charged amount, weight average molecular weight, and epoxy equivalent of each raw material are shown in Table 3.

[0060] [Table 3]

[0061] The abbreviations in Table 3 are as follows. Component (a1) GMA: glycidyl methacrylate (a2) Component CHMA: Cyclohexyl methacrylate (a3) Component CHMI: Cyclohexylmaleimide (Polymerization initiator) PHO: t-Hexylperoxy-2-ethylhexanoate (peroxide polymerization initiator manufactured by NOF Corp., product name: Perhexyl O) (solvent) PGMEA: Propylene glycol monomethyl ether acetate

[0062] <Synthesis Example 1: Synthesis of component (B) (B-1)> In a four-neck flask equipped with a thermometer, a reflux condenser, and a stirrer, 26.8 parts by mass of propylene glycol monomethyl ether acetate (PGMEA) as a solvent, 26.9 parts by mass of trimellitic acid (TMA) as a polycarboxylic acid, and 46.3 parts by mass of n-propyl vinyl ether (NPVE) as a vinyl ether were charged, and the mixture was heated with stirring to 80 ° C. Then, the mixture was stirred while maintaining the temperature, and after confirming that the acid value of the mixture reached 2.0 mg KOH / g or less, the reaction was terminated, and a 60% PGMEA solution of polycarboxylic acid hemiacetal ester (B-1) with an acid value of 0.6 mg KOH / g and an acid equivalent of 156 g / mol (active ingredient equivalent) was obtained.

[0063] <Acid value> The acid value was measured according to JIS K0070-1992 "Testing methods for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemical products."

[0064] <Synthesis Examples 2 to 3: Synthesis of polycarboxylic acid hemiacetal esters (B-2 to B-3)> The raw materials shown in Table 4 were mixed under the conditions shown in Table 4, and reaction products B-2 to B-3 were obtained in the same manner as in Synthesis Example 1. The amount of each raw material charged, the acid value, and the acid equivalent are shown in Table 4.

[0065] [Table 4]

[0066] The abbreviations in Table 4 are as follows. (Polycarboxylic Acid) TMA: Trimellitic acid PMA: Pyromellitic acid (Vinyl ether) NPVE: n-propyl vinyl ether IPVE: i-Propyl vinyl ether (solvent) PGMEA: Propylene glycol monomethyl ether acetate

[0067] <Examples 1 to 18 and Comparative Examples 1 to 8> Each component shown in Tables 5 to 7 was dissolved and mixed in the amount shown in Tables 5 to 7 to prepare coating solutions of thermosetting resin compositions for color filter protective films of Examples 1 to 18 and Comparative Examples 1 to 8. In Tables 5 to 7, the numerical values ​​showing the content of each component are parts by mass. The abbreviations in Tables 5 to 7 are as follows.

[0068] <(C) component> C-1: DOWSIL8019 (Dow Toray Co., Ltd., polyether modified product, Mw 19,000) C-2: Disparlon 1711EF (Kusumoto Chemicals Co., Ltd., polyether modified product, Mw 16,400) C-3: Silface SAG008 (manufactured by Nissin Chemical Industry Co., Ltd., polyether modified product, Mw10,100) <Multifunctional epoxy resin> EP157: Bisphenol A novolac type epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: "jER157S70", epoxy equivalent 210g / eq) <Other surfactants> C'-1: Megafac F-477 (DIC Corporation, fluorine-based) <Stabilizer> NPVE: n-propyl vinyl ether IPVE: i-Propyl vinyl ether <Additives> NMM: N-methylmorpholine <Solvent> PGMEA: Propylene Glycol Monomethyl Ether Acetate BAC: Butyl Acetate

[0069] The coating liquids of the thermosetting resin compositions of Examples 1 to 18 and Comparative Examples 1 to 8 were each filtered through a membrane filter (material: PE, pore size: 0.2 μm), and then further filtered through a hollow filter (material: PP, pore size: 0.02 μm). The obtained coating liquid of the thermosetting resin composition for the color filter protective film was spin-coated onto a substrate using a spin coater (model 1H-DX-2, manufactured by Mikasa Co., Ltd.). After coating, the substrate was pre-baked in a clean oven at 90°C for 2 minutes, and then post-baked in a clean oven at 230°C for 30 minutes to obtain a cured film with a predetermined film thickness. For the thermosetting resin composition or the obtained cured film, the following evaluations of "low residual metal ion property" and "NMP resistance" were performed. Also, the following evaluation of "coating property" was performed using the coating liquids of the thermosetting resin compositions of Examples 1 to 18 and Comparative Examples 1 to 8. The evaluation results are shown in Tables 5 to 7.

[0070] <Low residual metal ion property> For an alkali-free glass substrate (EAGLEXG, manufactured by Corning Inc.) on which a 1.0 μm thick cured film was formed, UV irradiation was performed using a UV cleaning device (Eye UV-ozone cleaning device, manufactured by Iwasaki Electric Co., Ltd.) with an irradiation dose of 5,000 mJ / cm 2 (converted to 254 nm), and then the substrate was immersed in a 0.05 wt% potassium hydroxide developer for 60 seconds. Thereafter, the substrate was washed with pure water for 10 seconds and dried sufficiently with an air blow. Using a fluorescent X-ray device (ZSX100e, manufactured by Rigaku Corporation), the residual potassium content on the surface of the cured film of this substrate was measured. When the residual potassium content was 0.4% or less, it was evaluated as ◎, when it exceeded 0.4% and was 0.6% or less, it was evaluated as 〇, and when it exceeded 0.6%, it was evaluated as ×. When the residual potassium content was ◎ or 〇, it was considered qualified.

[0071] <NMP resistance> 100 μL of NMP was dropped onto a 10 cm square alkali-free glass substrate (EAGLEXG, Corning) on ​​which a 1.0 μm thick cured film had been formed, and the substrate was covered with an 8 cm square cover glass and heated at 180°C for 15 minutes. After heating, the cover glass was removed and the NMP on the surface of the cured film was removed with an air blower. The film thickness of the cured film was measured before and after the test, and the rate of change in film thickness was calculated. When the rate of change in film thickness before and after the test was 25% or less, it was indicated as ◎, when it was more than 25% but not more than 30%, it was indicated as ◯, and when it was less than 30%, it was indicated as ◯. When the rate of change in film thickness before and after the test was rated as ⊚ or ◯, the film was rated as passed.

[0072] <Coatability (spin coating)> The coating solution of the thermosetting resin composition was applied to a 10 cm square non-alkali glass substrate (EAGELXG, Corning) under conditions that would result in a film thickness of 1.0 μm after curing, and then left to stand for 5 minutes in an environment of 23°C and 50% RH. If no liquid backflow was observed at the start of coating after standing, it was evaluated as ⊚, if the maximum width of liquid backflow was less than 2 mm, it was evaluated as ◯, and if the maximum width of liquid backflow was 2 mm or more, it was evaluated as ×. If liquid backflow was ⊚ or ◯, it was evaluated as passing.

[0073] <Coating properties (slit coating)> The coating solution of the thermosetting resin composition was applied to a 10 cm square alkali-free glass substrate (EAGELXG, Corning) starting from a point 2 cm away from one side using an applicator under conditions that the film thickness after curing would be 1.0 μm, and then the substrate was left to stand for 5 minutes in an environment of 23°C and 50% RH. If no liquid backflow was observed at the coating start point after standing, it was evaluated as ◎, if the maximum width of the liquid backflow was less than 2 mm, it was evaluated as ◯, and if the maximum width of the liquid backflow was 2 mm or more, it was evaluated as ×. If the liquid backflow was ◎ or ◯, it was evaluated as passing.

[0074] [Table 5]

[0075] [Table 6]

[0076] [Table 7]

[0077] From the results of Tables 5 and 6, in Examples 1 to 18, the cured film had good low metal ion residual property and NMP resistance, and the coating property of the coating solution of the thermosetting resin composition was good regardless of the coating method. On the other hand, from the results of Table 7, in Comparative Examples 1 and 2, component (C) was not used, so low metal ion residual property and coating property were insufficient. In Comparative Examples 3 to 6, component (A) was an epoxy group-containing polymer different from the configuration of the present invention, so NMP resistance was insufficient. Furthermore, in Comparative Examples 7 and 8, the functional group equivalent ratio of the carboxyl group of component (B) to the epoxy group in component (A) was too large or too small, so low metal ion residual property or NMP resistance was insufficient.

[0078] <Examples 19 to 42> The components shown in Tables 8 to 10 were dissolved and mixed in the amounts shown in Tables 8 to 10 to prepare coating solutions of thermosetting resin compositions for color filter protective films of Examples 19 to 42. In Tables 8 to 10, the values ​​showing the content of each component are in parts by mass. The abbreviations in Tables 8 to 10 are the same as those in Tables 5 to 7, except as follows. CHN: Cyclohexanone CPN: Cyclopentanone

[0079] The coating liquid of the thermosetting resin composition of Examples 19 to 42 was filtered through a membrane filter (material: PE, pore size: 0.2 μm), and then further filtered through a hollow filter (material: PP, pore size: 0.02 μm). The obtained coating liquid of the thermosetting resin composition for the color filter protective film was spin-coated on a substrate using a spin coater (model 1H-DX-2, manufactured by Mikasa Co., Ltd.). After coating, the substrate was pre-baked for 2 minutes in a clean oven at 90°C, and then post-baked for 30 minutes in a clean oven at 230°C to obtain a cured film with a predetermined film thickness. The above-mentioned "low metal ion residual property" and "NMP resistance" as well as the following "flatness (pattern substrate)" and "flatness (color filter substrate)" were evaluated for the thermosetting resin composition or the obtained cured film. In addition, the above-mentioned "coatability" was evaluated using the coating liquid of the thermosetting resin composition of Examples 19 to 42. The evaluation results are shown in Tables 8 to 10.

[0080] <Flatness (patterned substrate)> After forming a 1.0 μm thick cured film on a pattern substrate with L / S=150 μm / 50 μm and height of 2.5 μm, the surface step was measured with a stylus surface roughness meter (model EK4000AK, manufactured by Kosaka Laboratory Co., Ltd.). The flattening rate X was calculated from the maximum height difference (d1) of the pattern substrate before the cured film was formed and the maximum height difference (d2) after the cured film was formed according to the following calculation formula (1). A flattening rate of 85% or more before and after the test was evaluated as ◎, a rate of 80% or more but less than 85% was ◯, and a rate of less than 80% was ×. A flattening rate of ◎ or ○ before and after the test was evaluated as passing.

number

[0081] <Flatness (color filter substrate)> The height difference between the red pixel and the center of the green pixel, the height difference between the red pixel and the center of the blue pixel, and the height difference between the green pixel and the center of the blue pixel (pixel step) were obtained using a dummy color filter for flatness evaluation. After forming a 1.0 μm thick cured film on the color filter substrate, the height difference between the red pixel and the center of the green pixel, the height difference between the red pixel and the center of the blue pixel, and the height difference between the green pixel and the center of the blue pixel of the same part were obtained. These steps were measured with a stylus surface roughness meter (model EK4000AK, manufactured by Kosaka Laboratory Co., Ltd.). The larger value of the pixel step before the cured film formation was taken as the maximum pixel step before coating (d1), and the larger value of the pixel step after the cured film formation was taken as the maximum pixel step after coating (d2). The flattening rate X was calculated from these d1 and d2 using the following calculation formula (1). A flattening rate of 85% or more before and after the test was evaluated as ⊚, a flattening rate of 80% or more but less than 85% was evaluated as ◯, and a flattening rate of less than 80% was evaluated as x. A flattening rate of ⊚ or ◯ before and after the test was evaluated as passing.

number

[0082] [Table 8]

[0083] [Table 9]

[0084] [Table 10]

[0085] From the results of Tables 8 to 10, in Examples 19 to 41, the cured film had good low metal ion residual property, NMP resistance, and flatness, and the coating property of the coating liquid of the thermosetting resin composition was good regardless of the coating method. In Example 42, the cured film had good low metal ion residual property, NMP resistance, and flatness on the pattern substrate, and the coating property of the coating liquid of the thermosetting resin composition was good regardless of the coating method, but since no alicyclic ketone organic solvent was used in the organic solvent, the flatness on the color filter substrate was insufficient.

Claims

1. A thermosetting resin composition comprising an epoxy compound (A), a polyvalent carboxylic acid hemiacetal ester (B), and a silicone-based surfactant (C), The epoxy compound (A) includes an epoxy group-containing polymer having, as structural units, (a1) a (meth)acrylate monomer having an epoxy group, (a2) a monomer represented by the following formula (1), and (a3) ​​a monomer represented by the following formula (2), and having an epoxy equivalent of 155 to 240 g / mol: 【Chemistry 1】 (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 represents an aryl group or an alicyclic hydrocarbon group having 3 to 12 carbon atoms. 【Chemistry 2】 (In the formula, R 3 represents an alicyclic hydrocarbon group having 3 to 12 carbon atoms or an aromatic hydrocarbon group. the silicone surfactant (C) is 0.01 to 1.0 part by mass based on 100 parts by mass in total of the epoxy compound (A) and the polyvalent carboxylic acid hemiacetal ester (B); A thermosetting resin composition, characterized in that a functional group equivalent ratio of a carboxyl group of the polyvalent carboxylic acid hemiacetal ester (B) to a total epoxy group of the epoxy compound (A) is in the range of 0.25 to 0.

95.

2. Further, the composition contains an organic solvent, 2. The thermosetting resin composition according to claim 1, wherein the organic solvent contains an alicyclic ketone organic solvent in an amount of from 20% by mass to 80% by mass.

3. 3. A color filter comprising a protective film formed by curing the thermosetting resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Resin composition for color filter protective film, and color filter

    JP2011065051A

  • Thermosetting resin composition and color filter having hardened film of the same

    JP2022026360A

  • Thermosetting resin composition and color filter having cured film thereof

    JP2022112451A